Communalism in India : a challenge to theologizing - Arulsamy, S (Bangalore, Claretian Publications, 1988)
The statement, papers, and the proceedings of the Eleventh Annual Meeting of the Indian Theological Association, Bangalore, December 28th-31st, 1987
Keywords: Christianity.-- India.-- Congresses; Communalism; Communalism.-- India.-- Congresses; Conference papers and proceedings